Analysis Of The Readiness Of Sharia Banking Service Infrastructure In Efforts To Promote Financial Inclusion In Rural Areas (Case Study Of Suka Damai Timur Village, Langkat Regency) - Enjeli, Enjeli; Nasution, Muhammad Lathief Ilhamy; Nasution, Juliana (Universitas Pakuan, 2025)
This study was conducted to analyze the extent of service infrastructure readiness and identify and analyze what accessibility challenges occur in rural communities in accessing Islamic banking services in rural areas. This researcher uses a qualitative approach through interviews, as well as literacy studies which are then carried out in a data redaction process and analyzed descriptively. Primary data was obtained through an interview process with Islamic banking institutions and the community as well as the Suka Damai Timur village government institutions. The results of the study show that the infrastructure of Islamic banking services is still minimal. Where there are only 2 sub-branch offices and 4 ATM units spread across Langkat district, the level of community literacy is minimal and there is also no collaboration between local parties and Islamic banking institutions.